Servant Leadership Characteristics- Testing The Relability of Scale in Select Government Hospital - Malhotra, Meenakshi; Malik , Aanchal (Gyan Management Journal, 2024)
Purpose: The study is an attempt to test the standardization of a foreign scale on Servant Leadership Characteristics that is ‘The Organizational Leadership Assessment’ (OLA) (revised) evolved by James Alan Laub (1999) in selected Hospital Organization in Panchkula (India). Design/Methodology/ Approach: Specifically, as defined by James Alan Laub, the dimensions which are six in number that is a.) Values People, b.) Develops People, c.) Builds Community, d.) Displays Authenticity, e.) Provides Leadership and f.) Shares Leadership were used to build a servant leadership scale. The questionnaire was filled by 100 respondents from Panchkula (India). Further to test the reli ability and validity of it, Cronbach’s Alpha and Measures of Dispersion were used. Findings: The 6 dimensional measure of 60-items instrument main tains the Cronbach’s alpha for Servant leadership dimensions ranging between 0.879 - 0.921 which is above the significance level of 0.60. All the items have reliability above prescribed significance level, i.e.0.60. Practical Implication: It is anticipated that the Organizational Leadership Assessment will function as a valuable and significant resource for doing more study in various fields in the future.